2021
DOI: 10.1007/s00228-021-03218-6
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of cefotaxime in intensive care patients

Abstract: Purpose To characterise the pharmacokinetics and associated variability of cefotaxime in adult intensive care unit (ICU) patients and to assess the impact of patient covariates. Methods This work was based on data from cefotaxime-treated patients included in the ACCIS (Antibiotic Concentrations in Critical Ill ICU Patients in Sweden) study. Clinical data from 51 patients at seven different ICUs in Sweden, given cefotaxime (1000–3000 mg given 2–6 times dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Cefotaxime and desacetylcefotaxime are eliminated by the kidneys and estimated creatinine clearance (using eGFR) was able to be included on the clearance of cefotaxime. This finding concords with data from critically ill adult patients that have shown clearance to be proportional to estimated creatinine clearance 27 . No other studies have found an association between body surface area and clearance of desacetylcefotaxime, although a relationship between body surface area and liver volume has been recently identified in children 28 and this may account for the relationship identified for the metabolite in our study.…”
Section: Discussionsupporting
confidence: 74%
“…Cefotaxime and desacetylcefotaxime are eliminated by the kidneys and estimated creatinine clearance (using eGFR) was able to be included on the clearance of cefotaxime. This finding concords with data from critically ill adult patients that have shown clearance to be proportional to estimated creatinine clearance 27 . No other studies have found an association between body surface area and clearance of desacetylcefotaxime, although a relationship between body surface area and liver volume has been recently identified in children 28 and this may account for the relationship identified for the metabolite in our study.…”
Section: Discussionsupporting
confidence: 74%
“…In this heterogeneous study population, 2 significant covariates were found to be positively related to an increase in clearance, namely the eGFR and the albumin concentration. The effect of the eGFR is probably explained by the predominant renal clearance of cefotaxime and has also been identified by the studies of Swartling et al and Aardema et al 11,32 In the study of Swartling et al, a change in eGFR of 10 mL min À1 increased clearance by 0.74 L h À1 for eGFRs at or below 120 mL min À1 . In our exponential model, the increases in clearance are consistent with these result ranging from 0.42-0.99 L h À1 per 10 mL min À1 with a smaller increase in clearance at higher eGFRs.…”
Section: Discussionmentioning
confidence: 65%
“…21.6 L on average in healthy volunteers, which is probably due to expansion of the interstitial space because of capillary leakage combined with fluid loading 4,16–20 . Compared to a previous popPK study of cefotaxime as empirical treatment in critically ill patients, clearance was lower and volume of distribution higher 32 . The former might be explained by the high median eGFR of the patients included by Swartling et al .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations